Piezoelectric Sensor with a Helical Structure on the Thread Core - Park, Cheoleon; Kim, Hojoon; Cha, Youngsu (MDPI, 2020)
In this paper, we introduce a piezoelectric sensor curled on a thread core in a helical structure. In particular, a polyvinylidene fluoride film was curled and fixed on a thread core. A series of experiments were designed to deliver flexural loading to the piezoelectric sensor, to study its sensing characteristics. The experimental results show that the sensing output of the sensor is in phase with the applied flexural loading. In addition, the output voltage of the textile-based piezoelectric sensor was measured according to various flexural loadings. The flexural bending angle applied to the piezoelectric sensor is expected to be a power function of the voltage output. In addition, we demonstrate a smart textile by weaving the piezoelectric sensor.
Keywords: SMART; NANOGENERATOR